Utilizing AI (Artificial Intelligence) Platforms as Learning Media for MIPA Students at Palangka Raya University - Anatasya, Violina; Putra, Nandito; Triliyansi (JCER (Journal of Chemistry Education Research), 2025)
This research analyzes the use of AI (Artificial Intelligence) platform as a learning media for Mathematics and Natural Sciences Education students at Palangka Raya University. As technology develops, AI is often used in higher education as a system that mimics human intelligence. Various AI platforms have diverse functions that support student learning activities. The research method used descriptive qualitative with data collection through questionnaires on Google Form. The results show that students actively use AI, with ChatGPT being the most frequently used. AI makes it easier for students to obtain information quickly, makes the learning process more effective, and learning more interesting. However, there are risks of AI dependency and data inaccuracy. This research also describes the utilization of AI to contribute to improving the quality of learning for MIPA Education students at Palangka Raya University.